THE EFFECT OF LEARNING VIDEOS ON STUDENTS' LEARNING MOTIVATION - elamaysari sari (Teaching and General Education Studies, 2026)
The rapid development of information technology in education has encouraged the use of innovative and engaging learning media, particularly learning videos. Video-based learning media can present instructional material through audio-visual elements, making learning more interactive and easier for students to understand. This study aims to examine the effect of learning videos on students’ motivation and comprehension during the teaching and learning process. The method employed in this study was a literature review analyzing relevant books and scientific journal articles published between 2019 and 2024. The findings reveal that learning videos have a positive impact on the learning process. They enhance students’ interest, attention, participation, and motivation in classroom activities. Furthermore, the combination of visuals, audio, and animations helps students understand abstract or difficult concepts more effectively than verbal explanations alone. Therefore, learning videos can serve as an effective instructional medium to improve students’ motivation and understanding. Teachers are encouraged to integrate learning videos with appropriate teaching strategies to achieve optimal learning outcomes.